1994
DOI: 10.1148/radiology.191.3.8184071
|View full text |Cite
|
Sign up to set email alerts
|

Antemortem diagnosis of Baló concentric sclerosis: correlative MR imaging and pathologic features.

Abstract: Because MR imaging shows alternating ringlike lesions involving the deep and superficial white matter, which correspond to pathologic findings, it may play a central role in antemortem diagnosis of this rare disease, leaving more invasive diagnostic procedures for evaluation of equivocal cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…l0 In particular, the presentation of Baló's concentric sclerosis not infrequently mimics that of an intracerebral tumour. 8,9,11 On review of our patient's initial MRI scan, a pattern of concentric bands of different signal intensities was noted (Fig. 1B), as previously described in Baló's concentric sclerosis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…l0 In particular, the presentation of Baló's concentric sclerosis not infrequently mimics that of an intracerebral tumour. 8,9,11 On review of our patient's initial MRI scan, a pattern of concentric bands of different signal intensities was noted (Fig. 1B), as previously described in Baló's concentric sclerosis.…”
Section: Discussionsupporting
confidence: 74%
“…7 Antemortem diagnosis has also been made on the basis of characteristic MRI findings. 8,9 The initial provisional diagnosis in the present case was intracerebral tumour. It has been reported that multiple sclerosis plaques may occur as single large lesions that resemble a tumour radiologically.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This pathognomonic appearance is seen on both histopathology and MRI. 28 The demyelinating lesions in Schilder's disease are extensive, confluent, and asymmetric, involving both cerebral hemispheres with a peripheral rim of enhancement with contrast. 29,30 There may be involvement of the brain stem and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Balo termed the disease "encephalitis periaxialis concentrica", owing to the concentric pattern of the histological lesions. The advent of MRI has made it possible to diagnose the condition intra vitam, since the MRI appearance closely resembles autopsy findings [3,4]. We present the case of a male patient with a benign clinical course of relapsing-remitting motor and cognitive neurological deficits, with recurring and vanishing Balo-like lesions.…”
Section: Introductionmentioning
confidence: 92%